Exosome-Driven Antigen Transfer for MHC Class II Presentation Facilitated by the Receptor Binding Activity of Influenza Hemagglutinin - Testa, James S. (2010)
The mechanisms underlying MHC class I-restricted cross-presentation, the transfer of Ag from an infected cell to a professional APC, have been studied in great detail. Much less is known about the equivalent process for MHC class II-restricted presentation. After infection or transfection of class II-negative donor cells, we observed minimal transfer of a proteasome-dependent “class I-like” epitope within the influenza neuraminidase glycoprotein but potent transfer of a classical, H-2M–dependent epitope within the hemagglutinin (HA) glycoprotein. Additional experiments determined transfer to be exosome-mediated and substantially enhanced by the receptor binding activity of incorporated HA. Furthermore, a carrier effect was observed in that incorporated HA improved exosome-mediated transfer of a second membrane protein. This route of Ag presentation should be relevant to other enveloped viruses, may skew CD4(+) responses toward exosome-incorporated glycoproteins, and points toward novel vaccine strategies.